Hannah Arendt and theology - Kiess, John (Philosophy and theology, 2016)
A Public Philosopher : The Life and Thought of Hannah Arendt -- The Problem of Evil Reconsidered -- Amor Mundi : Worldliness, Love, and Citizenship -- "That a Beginning Be Made" : Natality, Action, and the Politics of Gratitude -- In the Region of the Spirit : Thinking Between Past and Future